Effects of age and gender on sweating pattern during exercise - Bar-Or, O. (International Journal of Sports Medicine, 1998)
Most research on human thermoregulation has focused on young adult males. Much less information is available regarding females, children and the elderly. The following is a brief review of factors that have impeded research in this field, as well as of the main age- and gender-related differences in sweating responses to the combined stresses of exercise and ambient heat. For more comprehensive reviews, see Drinkwater and Horvath (1975), Kenney (1985; 1995) and Bar-Or (1989; 1996).